The Implementation of Sinking Illegal Fishing Vessels Policy towards the Bilateral Relation between Indonesia – Malaysia: A Case Study in Tarakan - MADJID, M. Adnan; WIDODO, WIDODO; SAMUDRO, Eko G.; HERAWAN, Tutut (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
This study discusses the policy implementation by Indonesia regarding the sinking of illegal fishing vessels towards Indonesia's bilateral relations with Malaysia, especially those that occurred in Tarakan. Many losses from illegal fishing by neighboring countries made the President of Indonesia, took a firm stance regarding the rules of ship sinking to the accused ships that have been proven doing illegal fishing in the Indonesian sea. In this case, Malaysia is the country with the fifth largest fish commodity production in Southeast Asia whereas fish consumption in Malaysia is ranked first in the region. Thus, the country faces obstacles in fulfilling the need for fish faced with Indonesian policies in addressing illegal fishing arrests by foreign countries. By qualitative methods, this research reveals the background of the existence and implementation of policies for the sinking of illegal fishing vessels and the impact of these policies on the Malaysian state. International system pressure, state power and other theories were used to help carry out this research. As a result, this study provides an overview of the relationship between Indonesia and Malaysia after the enactment of the policy in order to support and improve the Indonesian Maritime Security.